Factories of Memory. - Tekin, Ozan (Diplomica Verlag, 2014)
12 September 1980, the third successful military coup in the history of Turkey has had a debilitating impact on the social, political and cultural life of the country. This study examines the representations of the 12 September coup through the lens of film as memory. Based on the content analysis of the two films, Beynelmilel (2006) and Bu Son Olsun (2012), and their reception, this study examines the representations of the 12 September military coup by means of the concepts of cultural memory, communicative and material memory (memory of objects), and construes whether the reconstruction of.